IMPLEMENTASI PENDEKATAN ANDRAGOGI DALAM PEMBELAJARAN PAKET B DI PKBM CITRA PRIANGAN - Wawan Hermawan; Diska Listianti; Rendi Kurniawan; Sherin Deviana Andara; Zahid Alhilmy (JCI Publisher, 2026)
Equality education through the Package B Program at PKBM has an important role in providing educational services for people who cannot access formal education. The diverse characteristics of learning residents require the application of appropriate learning approaches, one of which is through the andragogi approach. This study aims to analyze the implementation of the andragogy approach in Package B learning at PKBM Citra Priangan, identify its supporting and inhibiting factors, and determine its impact on the involvement of learning residents. The research uses a qualitative approach with a descriptive method. Data were collected through observation, semi-structured interviews, and documentation, then analyzed using Miles, Huberman's model. The results of the study show that the principles of andragogy have been applied through experiential learning, participatory methods, learning flexibility, and the development of life skills programs. Supporting factors include family culture, tutor competence, and learning flexibility, while inhibiting factors are limited facilities, learning environment conditions, and heterogeneity of learning residents. The implementation of andragogy has been proven to increase the participation, motivation, and involvement of learning residents in the learning process. Thus, the andragogy approach effectively supports the implementation of Package B learning that is more relevant to the needs of learning residents